3D printed functional nanomaterials for electrochemical energy storage. (August 2017) - Zhu, Cheng; Liu, Tianyu; Qian, Fang; Chen, Wen; Chandrasekaran, Swetha; Yao, Bin; Song, Yu; Duoss, Eric B.; Kuntz, Joshua D.; Spadaccini, Christopher M.; Worsley, Marcus A.; Li, Yat
Graphical abstract: Highlights: Laser-, lithography-, electrodeposition- and extrusion-based 3D printing techniques. 3D printed functional electrodes for electrochemical energy storage devices. Challenges and opportunities for 3D printing functional materials. Abstract: Electrochemical energy storage (EES) devices, such as lithium-ion batteries and supercapacitors, are emerging as primary power sources for global efforts to shift energy dependence from limited fossil fuels towards sustainable and renewable resources. These EES devices, while renowned for their high energy or power densities, portability, and long cycle life, are still facing significant performance hindrance due to manufacturing limitations. One major obstacle is the ability to engineer macroscopic components with designed and highly resolved nanostructures with optimal performance, via controllable and scalable manufacturing techniques. 3D printing covers several additive manufacturing methods that enable well-controlled creation of functional nanomaterials with three-dimensional architectures, representing a promising approach for fabrication of next-generation EES devices with high performance. In this review, we summarize recent progress in fabricating 3D functional electrodes utilizing 3D printing-based methodologies for EES devices. Specifically, laser-, lithography-, electrodeposition-, and extrusion-based 3D printing techniques are described and exemplified with examples from the literatures. Current challenges and future opportunities for functional materials fabrication via 3D printing techniques are also discussed.